Feito à mão: Histórias de artesãs de Uberlândia - Dalmônica, Mariely Gomes (2021)
This work presents the production process of the book Uberlândia . Feito à mão : histórias de artesãs de The product is formed by the profile of five artisans residing in the city of Uberlândia, in Minas Gerais: the embroiderer Lorena Tavares, the twin binders Reyla and Suellen Vilela, the street artist Carolina Clemente and the plastic artist Amanda Fonseca. The work aims to tell stories of young people who chose to work with handicrafts in the 21st century